PENGARUH PENAMBAHAN LIMBAH SERBUK KACA SEBAGAI FILLER MATERIAL PENGISI PADA CAMPURAN ASPHALT CONCRETE – WEARING COURSE (AC-WC) - Ibnu Sholichin (AGREGAT, 2022)
The need for good facilities and infrastructure is great for providing comfort to road users, as well as for reducing road accidents. Discarded old glass surfaces are waste products that will not disintegrate naturally from organic matter, thus employing alternative treatments to make the glass waste in the use of mixed materials a filler of the original bitumen.The method is the Marshall Test. The study of the planning of ashpalt concrete-wearing course using the method used by the Marshall method in referring to the 2018 and existing clan building rules. Stained-glass filler is carefully processed. At 5%, 6% and 7% to find optimum asphalt. From Marshall's test results came an optimum asphalt level of 6%. Filler count is 0%, 5%, 6% and 7%. From Marshall's test results with increased glass fillers obtained optimum filler levels at 5.17%. With a stable value of 2494.59 kg, flow of 5.83 mm, Marshall Quotient of 442.75 kg/mm, VIM by 3 %, VMA by 15,15% and VFA by 80%.The purpose of this study was to reduce the waste of glass and it is expected to be able to identify the effect of using the powdered waste products as a filling material on the mixture of asphalt, the value of the Marshall requirement (stabilizer, flow, VMA, VIM, VFB, Marshall Quotient) to a mixture of concrete asphalt containing glass waste products. Based on the 2018 specification of the building specifications of the concrete asphalt mix with the addition of glass filler fillers is relatively good.